Main chain fluorine-substituted cross-linked polymer solid electrolyte and preparation method and application thereof
By introducing the main chain fluorine crosslinked polymer into the polymer solid electrolyte, the problems of low ionic conductivity and poor oxidation stability of the existing electrolyte are solved, and the battery performance is improved, especially in terms of capacity retention and discharge capacity.
Patent Information
- Application Number
- CN202411901318.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing polymer solid electrolyte has low ion conductivity and poor oxidation stability under high operating potential environments, resulting in a degradation of battery performance.
The backbone fluorine crosslinked polymer solid electrolyte is prepared by crosslinked polymerization reaction of the reaction system of the backbone fluorine polyepoxy compound, the first lithium salt and an organic solvent to form an electrolyte with excellent ionic conductivity and oxidation stability.
The capacity retention rate and high discharge capacity of the battery have been improved, and the development of solid-state batteries have been promoted.
Smart Images

Figure CN119764543A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, and in particular to a main-chain fluorinated cross-linked polymer solid electrolyte and a preparation method and application thereof. Background Art
[0002] Solid electrolytes are one of the key materials in modern energy storage devices, especially solid-state lithium batteries. With the increasing requirements for high energy density and safety performance, solid electrolytes have received widespread attention as an ideal alternative to liquid electrolytes. Solid electrolytes can not only effectively avoid the leakage and flammability problems of liquid electrolytes, but also provide higher safety in high temperature environments. Among them, polymer solid electrolytes have become one of the more ideal electrolyte materials in solid-state batteries due to their good flexibility and processability.
[0003] However, existing polymer solid electrolytes still have some problems: (1) The ionic conductivity of polymer solid electrolytes is low, which will reduce the performance of the battery (such as discharge capacity, capacity retention rate, etc.); (2) Polymer solid electrolytes exhibit poor oxidative stability under high working potential environments, which may lead to decomposition of polymer solid electrolytes or reaction with electrode materials during the battery charging and discharging process, thereby reducing the performance of the battery (such as discharge capacity, capacity retention rate, etc.).
[0004] Therefore, how to obtain a polymer solid electrolyte with both excellent ionic conductivity and oxidation stability is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0005] The present invention provides a main chain fluorinated cross-linked polymer solid electrolyte, the main chain fluorinated cross-linked polymer solid electrolyte has excellent ionic conductivity and oxidation stability, and a battery containing the main chain fluorinated cross-linked polymer solid electrolyte has excellent capacity retention and high discharge capacity. Therefore, the main chain fluorinated cross-linked polymer solid electrolyte is of great significance for promoting the development of solid-state batteries.
[0006] The present invention also provides a method for preparing a main-chain fluorinated cross-linked polymer solid electrolyte, which can prepare a main-chain fluorinated cross-linked polymer solid electrolyte with excellent ionic conductivity and oxidation stability. The preparation method is simple in process and suitable for wide promotion and application.
[0007] The present invention also provides a battery, which comprises the main chain fluorinated cross-linked polymer solid electrolyte, so the battery has excellent capacity retention rate and high discharge capacity.
[0008] The first aspect of the present invention provides a main chain fluorinated cross-linked polymer solid electrolyte, which is obtained by cross-linking polymerization of a reaction system including a main chain fluorinated polyepoxy compound, a first lithium salt and an organic solvent;
[0009] The main chain fluorinated polyepoxy compound is at least one of the compounds shown in Formula 1, Formula 2, Formula 3, and Formula 4:
[0010]
[0011] In Formulas 1 to 4, n is independently an integer between 1 and 10 at each occurrence;
[0012] The first lithium salt is at least one of lithium difluorooxalatoborate, lithium tetrafluoroborate, and lithium hexafluorophosphate.
[0013] The main chain fluorinated cross-linked polymer solid electrolyte as described above, based on the total mass of the main chain fluorinated polyepoxy compound and the organic solvent, the content of the main chain fluorinated polyepoxy compound is 1wt% to 50wt%;
[0014] and / or, based on the total volume of the main chain fluorinated polyepoxy compound and the organic solvent, the concentration of the first lithium salt is 0.1 mol / L to 5 mol / L;
[0015] And / or, the organic solvent is at least one of ethylene carbonate, dimethyl carbonate, diethyl carbonate, propylene carbonate, ethyl methyl carbonate, dimethoxy carbonate, vinylene carbonate, dimethyl carbonate, fluoroethylene carbonate, fluoroethyl methyl carbonate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and 1,1,2,2-tetrafluoroethyl-2,2,3-trifluoroethyl ether.
[0016] The main chain fluorinated cross-linked polymer solid electrolyte as described above, the reaction system further comprises: an epoxy compound;
[0017] The epoxy compound is at least one of the compounds shown in Formula 5, Formula 6, Formula 7, Formula 8, Formula 9, and Formula 10:
[0018]
[0019] In equations 5 to 10, R 1 is independently selected at each occurrence from -H, -F, -Cl, -Br, -I, -(CF 2 ) x CF 3 、-CH 2 OCH 2 (CF 2 ) x CHF2 , -C y H 2y+1 or -OC y H 2y+1 , wherein x is an integer between 0 and 10, and y is an integer between 1 and 5.
[0020] The main chain fluorinated cross-linked polymer solid electrolyte as described above, based on the total molar content of the main chain fluorinated polyepoxy compound and the epoxy compound, the molar content of the main chain fluorinated polyepoxy compound is 1 mol% to 100 mol%, and the molar content of the epoxy compound is 0 mol% to 99 mol%.
[0021] The main chain fluorinated cross-linked polymer solid electrolyte as described above, the reaction system further comprises: a second lithium salt;
[0022] The second lithium salt is at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(fluoromethanesulfonate), lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonamide), and lithium perchlorate.
[0023] In the main chain fluorinated cross-linked polymer solid electrolyte as described above, based on the total volume of the main chain fluorinated polyepoxy compound and the organic solvent, the concentration of the second lithium salt is 0 mol / L to 5 mol / L.
[0024] The main chain fluorinated cross-linked polymer solid electrolyte as described above, the reaction system further comprises: an electrolyte additive;
[0025] The electrolyte additive is at least one of lithium difluorophosphate, lithium difluorobisoxalate phosphate, 2,3,4,5,6-pentafluorophenylboric acid, dibenzenesulfonimide, and tris(trimethylsilyl)phosphate.
[0026] In the main chain fluorinated cross-linked polymer solid electrolyte as described above, the content of the electrolyte additive is 0 wt % to 10 wt % based on the total mass of the main chain fluorinated polyepoxy compound, the first lithium salt and the organic solvent.
[0027] The second aspect of the present invention provides a method for preparing the main chain fluorinated cross-linked polymer solid electrolyte, comprising:
[0028] A first raw material system including a main chain fluorinated polyepoxy compound, a first lithium salt and an organic solvent is mixed to obtain a first precursor solution; or, a second raw material system including a main chain fluorinated polyepoxy compound, an epoxy compound, a first lithium salt and an organic solvent is mixed to obtain a second precursor solution; or, a third raw material system including a main chain fluorinated polyepoxy compound, a first lithium salt, a second lithium salt and an organic solvent is mixed to obtain a third precursor solution; or, a fourth raw material system including a main chain fluorinated polyepoxy compound, a first lithium salt, an organic solvent and an electrolyte additive is mixed to obtain a to a fourth precursor solution; or, mixing a fifth raw material system including a main chain fluorinated polyepoxy compound, an epoxy compound, a first lithium salt, an organic solvent and an electrolyte additive to obtain a fifth precursor solution; or, mixing a sixth raw material system including a main chain fluorinated polyepoxy compound, a first lithium salt, a second lithium salt, an organic solvent and an electrolyte additive to obtain a sixth precursor solution; or, mixing a seventh raw material system including a main chain fluorinated polyepoxy compound, an epoxy compound, a first lithium salt, a second lithium salt, an organic solvent and an electrolyte additive to obtain a seventh precursor solution;
[0029] The first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution, the fifth precursor solution, the sixth precursor solution, and the seventh precursor solution are respectively subjected to cross-linking polymerization reaction to obtain the main chain fluorinated cross-linked polymer solid electrolyte.
[0030] The third aspect of the present invention provides a battery comprising the main chain fluorinated cross-linked polymer solid electrolyte.
[0031] The main chain fluorinated cross-linked polymer solid electrolyte provided by the present invention is obtained by cross-linking polymerization of a reaction system including a main chain fluorinated polyepoxy compound, a first lithium salt and an organic solvent, and the prepared main chain fluorinated cross-linked polymer solid electrolyte has excellent ionic conductivity and oxidation stability, and a battery containing the main chain fluorinated cross-linked polymer solid electrolyte has excellent capacity retention and high discharge capacity. Therefore, the main chain fluorinated cross-linked polymer solid electrolyte is of great significance for promoting the development of solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1The state of the reaction precursor solution of Example 4 of the present invention before and after the cross-linking polymerization reaction, wherein: Figure 1 A is the state of the reaction precursor solution before the cross-linking polymerization reaction. Figure 1 B is the state of the reaction precursor solution after the cross-linking polymerization reaction;
[0034] Figure 2 This is the ionic conductivity test graph and linear sweep voltammogram of the main chain fluorinated cross-linked polymer solid electrolyte of Example 4 of the present invention, wherein: Figure 2 A is the ionic conductivity test graph of the main chain fluorinated cross-linked polymer solid electrolyte of Example 4, Figure 2 B is the linear sweep voltammogram of the main chain fluorinated cross-linked polymer solid electrolyte of Example 4;
[0035] Figure 3 This is a rate diagram of a battery comprising a main chain fluorinated cross-linked polymer solid electrolyte according to Example 4 of the present invention;
[0036] Figure 4 This is a cycle diagram of a battery comprising a main chain fluorinated cross-linked polymer solid electrolyte according to Example 4 of the present invention at a rate of 1C;
[0037] Figure 5 This is a cycle diagram of a battery containing an uncured electrolyte according to Comparative Example 1 of the present invention at a rate of 1C. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Unless otherwise specified, the raw materials and reagents used in the following examples can be obtained from commercial sources; the processes used, unless otherwise specified, are conventional processes in the art.
[0040] It should be noted that, the descriptions involving “first”, “second”, “third”, “fourth”, “fifth”, “sixth”, “seventh”, etc. in the present invention are only for descriptive purposes and therefore cannot be understood as limiting the present invention.
[0041] In the following examples, the term "epoxy compound" refers to a cyclic compound in which one or more of the ring atoms are oxygen atoms.
[0042] The term "main chain fluorinated polyepoxy compound" refers to an ether compound that satisfies both the requirements of containing a fluorine atom or a fluorinated functional group in the main chain and containing two or more epoxy groups.
[0043] The term "high voltage positive electrode" refers to a positive electrode with a charge termination voltage greater than 4V, such as a nickel cobalt manganese oxide lithium 811 positive electrode.
[0044] The first aspect of the present invention provides a main chain fluorinated cross-linked polymer solid electrolyte, which is obtained by cross-linking polymerization of a reaction system including a main chain fluorinated polyepoxy compound, a first lithium salt and an organic solvent;
[0045] The main chain fluorinated polyepoxy compound is at least one of the compounds shown in Formula 1, Formula 2, Formula 3, and Formula 4:
[0046]
[0047] In Formulas 1 to 4, n is independently an integer between 1 and 10 at each occurrence;
[0048] The first lithium salt is at least one of lithium difluorooxalatoborate, lithium tetrafluoroborate, and lithium hexafluorophosphate.
[0049] In the present invention, the main chain fluorinated cross-linked polymer solid electrolyte is obtained by dissolving the main chain fluorinated polyepoxy compound and the first lithium salt in an organic solvent and mixing them uniformly to obtain a precursor solution, and then subjecting the precursor solution to a cross-linking polymerization reaction.
[0050] The present invention applies the above-mentioned main chain fluorinated polyepoxy compound to a main chain fluorinated cross-linked polymer solid electrolyte, which has excellent ionic conductivity and oxidation stability, and the main chain fluorinated cross-linked polymer solid electrolyte can make the battery have excellent capacity retention rate and high discharge capacity.
[0051] In some embodiments, the first lithium salt may preferably be at least one of lithium difluorooxalatoborate and lithium tetrafluoroborate.
[0052] When the first lithium salt is the above-mentioned substance, the main chain fluorinated cross-linked polymer solid electrolyte has more excellent ionic conductivity and oxidative stability. The inventor analyzed this principle and believed that the reason may be that: the first lithium salt can dissociate lithium ions as carriers in the main chain fluorinated cross-linked polymer solid electrolyte, improving the ionic conductivity and oxidative stability of the main chain fluorinated cross-linked polymer solid electrolyte; the first lithium salt can decompose Lewis acid to initiate the cations of the main chain fluorinated polyepoxy compound to perform ring-opening polymerization, realizing the in-situ preparation of the main chain fluorinated cross-linked polymer solid electrolyte in the battery, which is beneficial to improving the ionic conductivity and oxidative stability of the main chain fluorinated cross-linked polymer solid electrolyte.
[0053] In a specific embodiment, based on the total mass of the main-chain fluorinated polyepoxy compound and the organic solvent, the content of the main-chain fluorinated polyepoxy compound is 1 wt % to 50 wt %.
[0054] When the content of the main chain fluorinated polyepoxy compound is within the above range, a main chain fluorinated cross-linked polymer solid electrolyte with high ionic conductivity can be obtained. In addition, the inventors have found through a large number of studies that when the content of the main chain fluorinated polyepoxy compound is less than 1wt%, the electrolyte after the cross-linking polymerization reaction is liquid and cannot be solidified; when the content of the main chain fluorinated polyepoxy compound is greater than 50wt%, the ionic conductivity of the obtained fluorinated cross-linked polymer solid electrolyte is low.
[0055] Exemplarily, based on the total mass of the main chain fluorinated polyepoxy compound and the organic solvent, the content of the main chain fluorinated polyepoxy compound can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt% %, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt%, 41wt%, 42wt%, 43wt%, 44wt%, 45wt%, 46wt%, 47wt%, 48wt%, 49wt% or 50wt%, any one of the above, and the range of any two.
[0056] In a specific embodiment, based on the total volume of the main chain fluorinated polyepoxy compound and the organic solvent, the concentration of the first lithium salt is 0.1 mol / L to 5 mol / L.
[0057] When the concentration of the first lithium salt is within the above range, a main chain fluorinated cross-linked polymer solid electrolyte with high ionic conductivity can be obtained. In addition, the inventors have found through research that when the concentration of the first lithium salt is less than 0.1 mol / L, the electrolyte after the cross-linking polymerization reaction is in a liquid state and cannot be solidified, and the cycle stability of the battery is deteriorated; when the concentration of the first lithium salt is greater than 5 mol / L, lithium dendrites are easily formed, resulting in poor stability of the electrolyte interface (SEI) of the main chain fluorinated cross-linked polymer solid electrolyte.
[0058] In a specific embodiment, the organic solvent is at least one of ethylene carbonate, dimethyl carbonate, diethyl carbonate, propylene carbonate, ethyl methyl carbonate, dimethoxy carbonate, vinylene carbonate, dimethyl carbonate, fluoroethylene carbonate, fluoroethyl methyl carbonate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and 1,1,2,2-tetrafluoroethyl-2,2,3-trifluoroethyl ether.
[0059] In a specific embodiment, the reaction system further comprises: an epoxy compound;
[0060] The epoxy compound is at least one of the compounds shown in Formula 5, Formula 6, Formula 7, Formula 8, Formula 9, and Formula 10:
[0061]
[0062] In Formulae 5 to 10, R1 is independently selected from -H, -F, -Cl, -Br, -I, -(CF 2 ) x CF 3 、-CH 2 OCH 2 (CF 2 ) x CHF 2 , -C y H 2y+1 or -OC y H 2y+1 , wherein x is an integer between 0 and 10, and y is an integer between 1 and 5.
[0063] In the present invention, the main chain fluorinated cross-linked polymer solid electrolyte can be obtained by cross-linking polymerization of a reaction system including a main chain fluorinated polyepoxy compound, an epoxy compound, a first lithium salt and an organic solvent. The obtained main chain fluorinated cross-linked polymer solid electrolyte has excellent ionic conductivity and oxidation stability.
[0064] In a specific embodiment, based on the total molar content of the main chain fluorinated polyepoxy compound and the epoxy compound, the molar content of the main chain fluorinated polyepoxy compound is 1 mol% to 100 mol%, and the molar content of the epoxy compound is 0 mol% to 99 mol%. Further, the molar content of the main chain fluorinated polyepoxy compound is 50 mol% to 100 mol%, and the molar content of the epoxy compound is 0 mol% to 50 mol%.
[0065] When the molar content of the main chain fluorinated polyepoxy compound and the molar content of the epoxy compound are respectively within the above ranges, a main chain fluorinated cross-linked polymer solid electrolyte with high ionic conductivity can be obtained. In addition, the inventors have found through research that when the molar content of the main chain fluorinated polyepoxy compound is less than 1 mol%, the electrolyte after the cross-linking polymerization reaction is liquid and cannot be solidified.
[0066] Exemplarily, based on the total molar content of the main chain fluorinated polyepoxy compound and the epoxy compound, when the content of the main chain fluorinated polyepoxy compound is 50 mol%, the molar content of the epoxy compound is 50 mol%; when the content of the main chain fluorinated polyepoxy compound is 60 mol%, the molar content of the epoxy compound is 40 mol%; when the content of the main chain fluorinated polyepoxy compound is 70 mol%, the molar content of the epoxy compound is 30 mol%; when the content of the main chain fluorinated polyepoxy compound is 80 mol%, the molar content of the epoxy compound is 20 mol%; when the content of the main chain fluorinated polyepoxy compound is 90 mol%, the molar content of the epoxy compound is 10 mol%; when the content of the main chain fluorinated polyepoxy compound is 100 mol%, the molar content of the epoxy compound is 0 mol%, etc.
[0067] In a specific embodiment, the reaction system further comprises: a second lithium salt;
[0068] The second lithium salt is at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(fluoromethanesulfonate), lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonamide), and lithium perchlorate.
[0069] In the present invention, the main chain fluorinated cross-linked polymer solid electrolyte can be obtained by a reaction system including a main chain fluorinated polyepoxy compound, a first lithium salt, a second lithium salt and an organic solvent through a cross-linking polymerization reaction, and the obtained main chain fluorinated cross-linked polymer solid electrolyte has excellent ionic conductivity and oxidation stability. It can also be obtained by a reaction system including a main chain fluorinated polyepoxy compound, an epoxy compound, a first lithium salt, a second lithium salt and an organic solvent through a cross-linking polymerization reaction, and the obtained main chain fluorinated cross-linked polymer solid electrolyte also has excellent ionic conductivity and oxidation stability.
[0070] In a specific embodiment, based on the total volume of the main chain fluorinated polyepoxy compound and the organic solvent, the concentration of the second lithium salt is 0 mol / L to 5 mol / L, for example, 0 mol / L, 0.1 mol / L, 0.5 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L or 5 mol / L, etc.
[0071] In a specific embodiment, the reaction system further comprises: an electrolyte additive;
[0072] The electrolyte additive is at least one of lithium difluorophosphate, lithium difluorobisoxalate phosphate, 2,3,4,5,6-pentafluorophenylboric acid, dibenzenesulfonimide, and tris(trimethylsilyl)phosphate.
[0073] In the present invention, the main chain fluorinated cross-linked polymer solid electrolyte can be obtained by a reaction system including a main chain fluorinated polyepoxy compound, a first lithium salt, an electrolyte additive and an organic solvent, and the obtained main chain fluorinated cross-linked polymer solid electrolyte has excellent ionic conductivity and oxidation stability. It can also be obtained by a reaction system including a main chain fluorinated polyepoxy compound, a first lithium salt, an epoxy compound, an electrolyte additive and an organic solvent, and the obtained main chain fluorinated cross-linked polymer solid electrolyte has excellent ionic conductivity and oxidation stability. It can also be obtained by a reaction system including a main chain fluorinated polyepoxy compound, a first lithium salt, a second lithium salt, an electrolyte additive and an organic solvent, and the obtained main chain fluorinated cross-linked polymer solid electrolyte also has excellent ionic conductivity and oxidation stability. It can also be obtained by a reaction system including a main chain fluorinated polyepoxy compound, a first lithium salt, a second lithium salt, an epoxy compound, an electrolyte additive and an organic solvent, and the obtained main chain fluorinated cross-linked polymer solid electrolyte also has excellent ionic conductivity and oxidation stability.
[0074] In a specific embodiment, based on the total mass of the main chain fluorinated polyepoxy compound, the first lithium salt and the organic solvent, the content of the electrolyte additive is 0wt% to 10wt%, for example, it can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, etc.
[0075] The second aspect of the present invention provides a method for preparing the main chain fluorinated cross-linked polymer solid electrolyte, comprising:
[0076] Mixing a first raw material system including a main chain fluorinated polyepoxy compound, a first lithium salt and an organic solvent to obtain a first precursor solution;
[0077] The first precursor solution is subjected to a cross-linking polymerization reaction to obtain the main chain fluorinated cross-linked polymer solid electrolyte.
[0078] In another specific embodiment, a second raw material system including a main chain fluorinated polyepoxy compound, an epoxy compound, a first lithium salt and an organic solvent is mixed to obtain a second precursor solution;
[0079] The second precursor solution is subjected to a cross-linking polymerization reaction to obtain the main chain fluorinated cross-linked polymer solid electrolyte.
[0080] In another specific embodiment, a third raw material system including a main chain fluorinated polyepoxy compound, a first lithium salt, a second lithium salt and an organic solvent is mixed to obtain a third precursor solution;
[0081] The third precursor solution is subjected to a cross-linking polymerization reaction to obtain the main chain fluorinated cross-linked polymer solid electrolyte.
[0082] In another specific embodiment, a fourth raw material system including a main chain fluorinated polyepoxy compound, a first lithium salt, an organic solvent, and an electrolyte additive is mixed to obtain a fourth precursor solution;
[0083] The fourth precursor solution is subjected to a cross-linking polymerization reaction to obtain the main chain fluorinated cross-linked polymer solid electrolyte.
[0084] In another specific embodiment, a fifth raw material system including a main chain fluorinated polyepoxy compound, an epoxy compound, a first lithium salt, an organic solvent, and an electrolyte additive is mixed to obtain a fifth precursor solution;
[0085] The fifth precursor solution is subjected to a cross-linking polymerization reaction to obtain the main chain fluorinated cross-linked polymer solid electrolyte.
[0086] In another specific embodiment, a sixth raw material system including a main chain fluorinated polyepoxy compound, a first lithium salt, a second lithium salt, an organic solvent, and an electrolyte additive is mixed to obtain a sixth precursor solution;
[0087] The sixth precursor solution is subjected to a cross-linking polymerization reaction to obtain the main chain fluorinated cross-linked polymer solid electrolyte.
[0088] In another specific embodiment, a seventh raw material system including a main chain fluorinated polyepoxy compound, an epoxy compound, a first lithium salt, a second lithium salt, an organic solvent, and an electrolyte additive is mixed to obtain a seventh precursor solution;
[0089] The seventh precursor solution is subjected to a cross-linking polymerization reaction to obtain the main chain fluorinated cross-linked polymer solid electrolyte.
[0090] The present invention adopts the above preparation methods to prepare main chain fluorinated cross-linked polymer solid electrolyte with excellent ionic conductivity and oxidation stability.
[0091] In some embodiments, the cross-linking polymerization reaction is carried out at a temperature of 30° C. to 80° C. and for a time of 6 hours to 48 hours.
[0092] When the temperature and time parameters of the cross-linking polymerization reaction are respectively within the above ranges, a main-chain fluorinated cross-linked polymer solid electrolyte having better ionic conductivity and oxidation stability can be prepared.
[0093] Exemplarily, the temperature for carrying out the cross-linking polymerization reaction can be 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, or any range consisting of any two thereof;
[0094] The time can be 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours, 28 hours, 29 hours, 30 hours, 31 hours, 32 hours, 33 hours, 34 hours, 35 hours, 36 hours, 37 hours, 38 hours, 39 hours, 40 hours, 41 hours, 42 hours, 43 hours, 44 hours, 45 hours, 46 hours, 47 hours or 48 hours, any one of them, and a range consisting of any two of them.
[0095] The third aspect of the present invention provides a battery, comprising the above-mentioned main chain fluorinated cross-linked polymer solid electrolyte. Therefore, the main chain fluorinated cross-linked polymer solid electrolyte has excellent ionic conductivity and oxidation stability, and the battery comprising the main chain fluorinated cross-linked polymer solid electrolyte has excellent capacity retention and high discharge capacity.
[0096] In a specific embodiment, the battery further includes a positive electrode, a negative electrode, and a separator.
[0097] In some embodiments, the positive electrode is at least one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese oxide, and lithium-rich manganese base.
[0098] In some embodiments, the negative electrode is at least one of lithium metal, graphite, silicon carbon, and silicon.
[0099] In some embodiments, the membrane is at least one of polyethylene film, polypropylene film, nylon nonwoven membrane, seaweed fiber nonwoven membrane, cellulose membrane, bacterial cellulose membrane, glass fiber membrane, polyethylene terephthalate membrane, polyimide nonwoven membrane, polyamide membrane, spandex membrane, and aramid membrane.
[0100] The present invention is further described below through specific embodiments.
[0101] Example 1
[0102] In this embodiment, a main-chain fluorinated cross-linked polymer solid electrolyte and a battery containing the main-chain fluorinated cross-linked polymer solid electrolyte are prepared by the following process:
[0103] In an argon-filled glove box, 1,4-bis(2',3'-epoxypropyl)perfluorobutane (BEPFB), lithium difluorooxalatoborate (LiDFOB), lithium tetrafluoroborate (LiBF 4), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and lithium difluorophosphate (LiDFP) are dissolved in fluoroethylene carbonate (FEC), and stirred evenly to obtain a reaction precursor solution; the reaction precursor solution is added to a battery shell with lithium nickel cobalt manganese oxide 811 as a positive electrode, lithium metal as a negative electrode, and a polyethylene film as a separator, and then the reaction precursor solution in the battery shell is subjected to a cross-linking polymerization reaction at 60°C for 24 hours to obtain a main chain fluorinated cross-linked polymer solid electrolyte and a battery comprising the main chain fluorinated cross-linked polymer solid electrolyte.
[0104] The raw materials and addition amounts used to prepare the main chain fluorinated cross-linked polymer solid electrolyte in this embodiment are shown in Table 1:
[0105] Table 1 Raw materials and addition amount of main chain fluorinated cross-linked polymer solid electrolyte
[0106]
[0107] Example 2
[0108] In this embodiment, a main-chain fluorinated cross-linked polymer solid electrolyte and a battery containing the main-chain fluorinated cross-linked polymer solid electrolyte are prepared by the following process:
[0109] In a glove box filled with argon, 1,4-bis(2',3'-epoxypropyl)perfluorobutane (BEPFB), lithium difluorooxalatoborate (LiDFOB), lithium bis(trifluoromethylsulfonyl imide) (LiTFSI) and lithium difluorophosphate (LiDFP) are dissolved in a mixed solvent of fluoroethylene carbonate (FEC) and fluoroethyl methyl carbonate (FEMC), and stirred evenly to obtain a reaction precursor solution; the reaction precursor solution is added to a battery shell with lithium nickel cobalt manganese oxide 811 as a positive electrode, lithium metal as a negative electrode, and a polyethylene film as a separator, and then the reaction precursor solution in the battery shell is subjected to a cross-linking polymerization reaction at 60° C. for 24 hours to obtain a main chain fluorinated cross-linked polymer solid electrolyte and a battery containing the main chain fluorinated cross-linked polymer solid electrolyte.
[0110] The raw materials and addition amounts used to prepare the main chain fluorinated cross-linked polymer solid electrolyte in this embodiment are shown in Table 2:
[0111] Table 2 Raw materials and addition amount of main chain fluorinated cross-linked polymer solid electrolyte
[0112]
[0113] Example 3
[0114] The process of preparing the main chain fluorinated cross-linked polymer solid electrolyte and the battery comprising the main chain fluorinated cross-linked polymer solid electrolyte in this embodiment is basically the same as that in embodiment 2, except that:
[0115] 1,4-bis(2',3'-epoxypropyl)perfluorobutane (BEPFB), lithium difluorooxalatoborate (LiDFOB), lithium tetrafluoroborate (LiBF 4 ), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and dibenzenesulfonyl imide (BBSI) are dissolved in a mixed solvent of fluoroethylene carbonate (FEC) and fluoroethyl methyl carbonate (FEMC), and stirred evenly to obtain a reaction precursor solution.
[0116] The raw materials and addition amounts used to prepare the main chain fluorinated cross-linked polymer solid electrolyte in this embodiment are shown in Table 3:
[0117] Table 3 Raw materials and addition amount of main chain fluorinated cross-linked polymer solid electrolyte
[0118]
[0119]
[0120] Example 4
[0121] The process of preparing the main chain fluorinated cross-linked polymer solid electrolyte and the battery comprising the main chain fluorinated cross-linked polymer solid electrolyte in this embodiment is basically the same as that in embodiment 2, except that:
[0122] 1,4-bis(2',3'-epoxypropyl)perfluorobutane (BEPFB), lithium difluorooxalatoborate (LiDFOB), lithium tetrafluoroborate (LiBF 4 ), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and lithium difluorophosphate (LiDFP) are dissolved in a mixed solvent of fluoroethylene carbonate (FEC) and fluoroethyl methyl carbonate (FEMC), and stirred evenly to obtain a reaction precursor solution.
[0123] The raw materials and addition amounts used to prepare the main chain fluorinated cross-linked polymer solid electrolyte in this embodiment are shown in Table 4:
[0124] Table 4 Raw materials and addition amount of main chain fluorinated cross-linked polymer solid electrolyte
[0125]
[0126] Example 5
[0127] The process of preparing the main chain fluorinated cross-linked polymer solid electrolyte and the battery comprising the main chain fluorinated cross-linked polymer solid electrolyte in this embodiment is basically the same as that in embodiment 4, except that:
[0128] Octafluoro-1,6-hexanediol diglycidyl ether (OFHDGE), lithium difluorooxalatoborate (LiDFOB), lithium tetrafluoroborate (LiBF 4 ), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and lithium difluorophosphate (LiDFP) are dissolved in a mixed solvent of fluoroethylene carbonate (FEC) and fluoroethyl methyl carbonate (FEMC), and stirred evenly to obtain a reaction precursor solution.
[0129] The raw materials and addition amounts used to prepare the main chain fluorinated cross-linked polymer solid electrolyte in this embodiment are shown in Table 5:
[0130] Table 5 Raw materials and addition amount of main chain fluorinated cross-linked polymer solid electrolyte
[0131]
[0132] Example 6
[0133] The process of preparing the main chain fluorinated cross-linked polymer solid electrolyte and the battery comprising the main chain fluorinated cross-linked polymer solid electrolyte in this embodiment is basically the same as that in embodiment 4, except that:
[0134] 1,4-bis(2',3'-epoxypropyl)perfluorobutane (BEPFB), monomer trifluoropropylene oxide (TFPO), lithium difluorooxalatoborate (LiDFOB), lithium tetrafluoroborate (LiBF 4 ), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and lithium difluorophosphate (LiDFP) are dissolved in a mixed solvent of fluoroethylene carbonate (FEC) and fluoroethyl methyl carbonate (FEMC), and stirred evenly to obtain a reaction precursor solution.
[0135] The raw materials and addition amounts used to prepare the main chain fluorinated cross-linked polymer solid electrolyte in this embodiment are shown in Table 6:
[0136] Table 6 Raw materials and addition amount of main chain fluorinated cross-linked polymer solid electrolyte
[0137]
[0138] Example 7
[0139] The process of preparing the main chain fluorinated cross-linked polymer solid electrolyte and the battery comprising the main chain fluorinated cross-linked polymer solid electrolyte in this embodiment is basically the same as that in embodiment 4, except that:
[0140] 1,4-bis(2',3'-epoxypropyl)perfluorobutane (BEPFB), monomer 1,3-dioxolane (DOL), lithium difluorooxalatoborate (LiDFOB), lithium tetrafluoroborate (LiBF 4), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and lithium difluorophosphate (LiDFP) are dissolved in a mixed solvent of fluoroethylene carbonate (FEC) and fluoroethyl methyl carbonate (FEMC), and stirred evenly to obtain a reaction precursor solution.
[0141] The raw materials and addition amounts used to prepare the main chain fluorinated cross-linked polymer solid electrolyte in this embodiment are shown in Table 7:
[0142] Table 7 Raw materials and addition amount of main chain fluorinated cross-linked polymer solid electrolyte
[0143]
[0144] Example 8
[0145] The process of preparing the main chain fluorinated cross-linked polymer solid electrolyte and the battery comprising the main chain fluorinated cross-linked polymer solid electrolyte in this embodiment is basically the same as that in embodiment 4, except that:
[0146] Octafluoro-1,6-hexanediol diglycidyl ether (OFHDGE), monomer trifluoropropylene oxide (TFPO), lithium difluorooxalatoborate (LiDFOB) and dibenzenesulfonimide (BBSI) are dissolved in a mixed solvent of fluoroethylene carbonate (FEC) and fluoroethyl methyl carbonate (FEMC), and stirred uniformly to obtain a reaction precursor solution.
[0147] The raw materials and addition amounts used to prepare the main chain fluorinated cross-linked polymer solid electrolyte in this embodiment are shown in Table 8:
[0148] Table 8 Raw materials and addition amount of main chain fluorinated cross-linked polymer solid electrolyte
[0149]
[0150] Example 9
[0151] The process of preparing the main chain fluorinated cross-linked polymer solid electrolyte and the battery comprising the main chain fluorinated cross-linked polymer solid electrolyte in this embodiment is basically the same as that in embodiment 4, except that:
[0152] 1,4-bis(2',3'-epoxypropyl)perfluorobutane (BEPFB), lithium difluorooxalatoborate (LiDFOB), lithium tetrafluoroborate (LiBF 4 ) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) are dissolved in a mixed solvent of fluoroethylene carbonate (FEC) and fluoroethyl methyl carbonate (FEMC), and stirred evenly to obtain a reaction precursor solution.
[0153] The raw materials and addition amounts used to prepare the main chain fluorinated cross-linked polymer solid electrolyte in this embodiment are shown in Table 9:
[0154] Table 9 Raw materials and addition amount of main chain fluorinated cross-linked polymer solid electrolyte
[0155]
[0156]
[0157] Comparative Example 1
[0158] The process of preparing the uncured electrolyte (an electrolyte that is liquid and cannot be cured after cross-linking polymerization) and the battery containing the uncured electrolyte in this comparative example is basically the same as that in Example 4, except that:
[0159] Ethylene glycol diglycidyl ether (EGDE), lithium difluorooxalatoborate (LiDFOB), lithium tetrafluoroborate (LiBF 4 ), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and lithium difluorophosphate (LiDFP) are dissolved in a mixed solvent of fluoroethylene carbonate (FEC) and fluoroethyl methyl carbonate (FEMC), and stirred evenly to obtain a reaction precursor solution.
[0160] The raw materials and addition amounts used to prepare the uncured electrolyte in this comparative example are shown in Table 10:
[0161] Table 10 Raw materials and addition amount of uncured electrolyte
[0162]
[0163] Comparative Example 2
[0164] The process of preparing the uncured electrolyte (an electrolyte that is liquid and cannot be cured after cross-linking polymerization) and the battery containing the uncured electrolyte in this comparative example is basically the same as that in Example 4, except that:
[0165] The monomers trifluoropropylene oxide (TFPO), lithium difluorooxalatoborate (LiDFOB), lithium tetrafluoroborate (LiBF 4 ), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and lithium difluorophosphate (LiDFP) are dissolved in a mixed solvent of fluoroethylene carbonate (FEC) and fluoroethyl methyl carbonate (FEMC), and stirred evenly to obtain a reaction precursor solution.
[0166] The raw materials and addition amounts used to prepare the uncured electrolyte in this comparative example are shown in Table 11:
[0167] Table 11 Raw materials and addition amount of uncured electrolyte
[0168]
[0169] Performance Testing
[0170] The following performance tests were performed on the batteries containing the main chain fluorinated cross-linked polymer solid electrolyte of Examples 1-9 and the batteries containing the uncured electrolyte of Comparative Examples 1-2 under the test conditions of 1C rate and a test voltage range of 2.8-4.5V, respectively. The test results are shown in Table 12;
[0171] Ionic conductivity (mS / cm): obtained by electrochemical impedance spectroscopy of the battery using an electrochemical workstation;
[0172] Oxidation stability potential (V): obtained by performing linear sweep voltammetry test on the battery using an electrochemical workstation;
[0173] Discharge capacity (mAh cm -2 ): The battery is tested by constant current charging and discharging of the battery using a battery testing system;
[0174] Capacity retention rate (%): Calculated by dividing the discharge capacity at a specified number of cycles by the maximum discharge capacity.
[0175] Table 12 Test results
[0176]
[0177] “—” in the table means that the ionic conductivity of the uncured electrolyte was not tested.
[0178] As can be seen from Table 12, the main chain fluorinated cross-linked polymer solid electrolyte of the present invention has an ionic conductivity of 1.0mS / cm to 2.8mS / cm at room temperature and an oxidation stability potential of 5.4V to 5.6V, which can effectively improve the discharge capacity and capacity retention rate of the battery. This may be because: (1) the fluorine atom in the main chain is a strong electron-withdrawing group, which can reduce the highest occupied molecular energy level of the polymer, thereby enhancing the oxidation stability of the main chain fluorinated cross-linked polymer solid electrolyte; (2) multiple epoxy functional groups can also introduce ether oxygen bonds into the chain segments, improve the lithium ion transmission capacity of the polymer, and ensure the high ionic conductivity of the main chain fluorinated cross-linked polymer solid electrolyte; (3) multiple epoxy functional groups can be used as active functional groups for cation ring-opening polymerization, realize the in-situ preparation of the polymer in the battery, ensure the close contact between the main chain fluorinated cross-linked polymer solid electrolyte and the interface between the positive and negative electrodes, which is conducive to improving the discharge capacity and capacity retention rate of the battery. By comparing Comparative Example 1, Comparative Example 2 and Example 4, it can be seen that when 1,4-bis(2',3'-epoxypropyl)perfluorobutane (BEPFB) is replaced with ethylene glycol diglycidyl ether (EGDE) or monomer trifluoropropylene oxide (TFPO), the prepared electrolyte is in an uncured state, and the oxidation stability potential of the electrolyte is reduced, and the discharge capacity and capacity retention rate of the battery are reduced, indicating that adding BEPFB to the electrolyte can effectively increase the oxidation stability potential of the electrolyte, and increase the discharge capacity and capacity retention rate of the battery. Therefore, the main chain fluorinated cross-linked polymer solid electrolyte prepared by the present invention has excellent ionic conductivity and oxidation stability, and the battery containing the main chain fluorinated cross-linked polymer solid electrolyte has excellent capacity retention rate and high discharge capacity.
[0179] in addition, Figure 1 The state of the reaction precursor solution of Example 4 before and after the cross-linking polymerization reaction, wherein: Figure 1 A is the state of the reaction precursor solution before the cross-linking polymerization reaction. Figure 1 B is the state of the reaction precursor solution after the cross-linking polymerization reaction;
[0180] from Figure 1 It can be seen that the reaction precursor solution before the cross-linking polymerization reaction ( Figure 1 A) is in liquid state, and after cross-linking polymerization reaction ( Figure 1 B) is firmly attached to the wall of the glass bottle, and even when inverted, the main chain fluorinated cross-linked polymer solid electrolyte will not fall off the wall.
[0181] Figure 2 The ionic conductivity test graph and linear sweep voltammogram of the main chain fluorinated cross-linked polymer solid electrolyte of Example 4 are shown in FIG. Figure 2A is the ionic conductivity test graph of the main chain fluorinated cross-linked polymer solid electrolyte of Example 4, Figure 2 B is the linear sweep voltammogram of the main chain fluorinated cross-linked polymer solid electrolyte of Example 4;
[0182] Depend on Figure 2 It can be seen from A that the ionic conductivity of the fluorinated cross-linked polymer solid electrolyte is 1 mS / cm. In addition, the present invention also conducted the same test on the fluorinated cross-linked polymer solid electrolytes of Examples 1-3 and Examples 5-9. The specific results are shown in Table 2, and all of them can achieve the effect of high ionic conductivity of 1.0 mS / cm to 2.8 mS / cm, which shows that the fluorinated cross-linked polymer solid electrolyte provided by the present invention has excellent ionic conductivity;
[0183] Depend on Figure 2 It can be seen from B that the oxidation stability potential of the fluorinated cross-linked polymer solid electrolyte can reach 5.6V, which shows that the fluorinated cross-linked polymer solid electrolyte has excellent oxidation stability and can withstand a positive electrode with a high working potential (i.e., a high-voltage positive electrode nickel cobalt manganese oxide lithium 811).
[0184] Figure 3 is a rate diagram of a battery comprising a main chain fluorinated cross-linked polymer solid electrolyte of Example 4;
[0185] Depend on Figure 3 It can be seen that the main chain fluorinated cross-linked polymer solid electrolyte can release higher capacity even at higher rates.
[0186] Figure 4 4 is a cycle diagram of a battery comprising a main chain fluorinated cross-linked polymer solid electrolyte at a rate of 1C;
[0187] Depend on Figure 4 It can be seen that even if the positive electrode is lithium nickel cobalt manganese oxide 811, the capacity retention rate of the battery containing the main chain fluorinated cross-linked polymer solid electrolyte can still be as high as 83.8% after 1000 cycles at a rate of 1C, indicating that the battery containing the main chain fluorinated cross-linked polymer solid electrolyte of the present invention can still exhibit excellent cycle stability for the high-voltage positive electrode.
[0188] Figure 5 1 is a cycle diagram of a battery containing an uncured electrolyte of Comparative Example 1 at a rate of 1C;
[0189] Depend on Figure 5 It can be seen that after 600 cycles at 1C rate, the capacity retention rate of the battery assembled with the uncured electrolyte obtained by in-situ polymerization of the non-fluorinated polyepoxy compound drops to 49.2%.
[0190] In summary, the main chain fluorinated cross-linked polymer solid electrolyte prepared by the present invention has close contact with the electrode interface, has excellent ionic conductivity and oxidation stability, and shows high stability to the high-voltage positive electrode, so that the battery containing the main chain fluorinated cross-linked polymer solid electrolyte shows excellent cycle stability.
[0191] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A main chain fluorinated cross-linked polymer solid electrolyte, characterized in that: It is obtained by cross-linking polymerization of a reaction system including a main chain fluorinated polyepoxy compound, a first lithium salt and an organic solvent; The main chain fluorinated polyepoxy compound is at least one of the compounds shown in Formula 1, Formula 2, Formula 3, and Formula 4: In Formulas 1 to 4, n is independently an integer between 1 and 10 at each occurrence; The first lithium salt is at least one of lithium difluorooxalatoborate, lithium tetrafluoroborate, and lithium hexafluorophosphate.
2. The main chain fluorinated cross-linked polymer solid electrolyte according to claim 1, characterized in that: Based on the total mass of the main chain fluorinated polyepoxy compound and the organic solvent, the content of the main chain fluorinated polyepoxy compound is 1 wt% to 50 wt%; and / or, based on the total volume of the main chain fluorinated polyepoxy compound and the organic solvent, the concentration of the first lithium salt is 0.1 mol / L to 5 mol / L; And / or, the organic solvent is at least one of ethylene carbonate, dimethyl carbonate, diethyl carbonate, propylene carbonate, ethyl methyl carbonate, dimethoxy carbonate, vinylene carbonate, dimethyl carbonate, fluoroethylene carbonate, fluoroethyl methyl carbonate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and 1,1,2,2-tetrafluoroethyl-2,2,3-trifluoroethyl ether.
3. The main chain fluorinated cross-linked polymer solid electrolyte according to claim 1, characterized in that: The reaction system further comprises: an epoxy compound; The epoxy compound is at least one of the compounds shown in Formula 5, Formula 6, Formula 7, Formula 8, Formula 9, and Formula 10: In Formulae 5 to 10, R1 is independently selected from -H, -F, -Cl, -Br, -I, -(CF2) at each occurrence. x CF3, -CH2OCH2(CF2) x CHF2, -C y H 2y+1 or -OC y H 2y+1 , wherein x is an integer between 0 and 10, and y is an integer between 1 and 5.
4. The main chain fluorinated cross-linked polymer solid electrolyte according to claim 3, characterized in that: Based on the total molar content of the main chain fluorinated polyepoxy compound and the epoxy compound, the molar content of the main chain fluorinated polyepoxy compound is 1 mol% to 100 mol%, and the molar content of the epoxy compound is 0 mol% to 99 mol%.
5. The main chain fluorinated cross-linked polymer solid electrolyte according to claim 1 or 3, characterized in that: The reaction system further comprises: a second lithium salt; The second lithium salt is at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(fluoromethanesulfonate), lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonamide), and lithium perchlorate.
6. The main chain fluorinated cross-linked polymer solid electrolyte according to claim 5, characterized in that: Based on the total volume of the main-chain fluorinated polyepoxy compound and the organic solvent, the concentration of the second lithium salt is 0 mol / L to 5 mol / L.
7. The main chain fluorinated cross-linked polymer solid electrolyte according to any one of claims 1, 3 and 5, characterized in that: The reaction system further comprises: an electrolyte additive; The electrolyte additive is at least one of lithium difluorophosphate, lithium difluorobisoxalate phosphate, 2,3,4,5,6-pentafluorophenylboric acid, dibenzenesulfonimide, and tris(trimethylsilyl)phosphate.
8. The main chain fluorinated cross-linked polymer solid electrolyte according to claim 7, characterized in that: Based on the total mass of the main-chain fluorinated polyepoxy compound, the first lithium salt and the organic solvent, the content of the electrolyte additive is 0 wt % to 10 wt %.
9. A method for preparing a main chain fluorinated cross-linked polymer solid electrolyte according to any one of claims 1 to 8, characterized in that: include: Mixing a first raw material system including a main chain fluorinated polyepoxy compound, a first lithium salt and an organic solvent to obtain a first precursor solution; Or, a second raw material system including a main chain fluorinated polyepoxy compound, an epoxy compound, a first lithium salt and an organic solvent is mixed to obtain a second precursor solution; or, a third raw material system including a main chain fluorinated polyepoxy compound, a first lithium salt, a second lithium salt and an organic solvent is mixed to obtain a third precursor solution; or, a fourth raw material system including a main chain fluorinated polyepoxy compound, a first lithium salt, an organic solvent and an electrolyte additive is mixed to obtain a fourth precursor solution; or, a fifth raw material system including a main chain fluorinated polyepoxy compound, an epoxy compound, a first lithium salt, an organic solvent and an electrolyte additive is mixed to obtain a fifth precursor solution; or, a sixth raw material system including a main chain fluorinated polyepoxy compound, a first lithium salt, a second lithium salt, an organic solvent and an electrolyte additive is mixed to obtain a sixth precursor solution; or, a seventh raw material system including a main chain fluorinated polyepoxy compound, an epoxy compound, a first lithium salt, a second lithium salt, an organic solvent and an electrolyte additive is mixed to obtain a seventh precursor solution; The first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution, the fifth precursor solution, the sixth precursor solution, and the seventh precursor solution are respectively subjected to cross-linking polymerization reaction to obtain the main chain fluorinated cross-linked polymer solid electrolyte.
10. A battery, characterized in that: The invention comprises the main chain fluorinated cross-linked polymer solid electrolyte as claimed in any one of claims 1 to 8.
Citation Information
Patent Citations
Polymer, crosslinked polymer, composition for solid polymer electrolyte, solid polymer electrolyte and adhesive composition
CN101107282A
Solid polymer electrolyte and battery preparation method thereof
CN115732754A
Fluorine-substituted cross-linked polymer solid electrolyte, solid-state battery and preparation method thereof
CN117304467A
Solid polymer electrolyte, preparation method and solid-state battery
CN117393849A
Cross-linked polymer, synthetic method of cross-linked polymer and solid polymer electrolyte
CN117887109A